Novel kissing catheter technique for foreign body retrieval - Vinay R Jaiswal; Charan P Lanjewar; Milind S Phadke; Prafulla G Kerkar (Wolters Kluwer Medknow Publications, 2014)
We report a novel technique 'the kissing catheter technique' for retrieval of a broken catheter fragment in a patient undergoing closure of a patent ductus arteriosus.